2009
DOI: 10.1021/jp904841j
|View full text |Cite
|
Sign up to set email alerts
|

Charge Mobility and Transport Behavior in the Ordered and Disordered States of the Regioregular Poly(3-hexylthiophene)

Abstract: We theoretically analyze the charge-transfer behavior of regioregular poly(3-hexylthiophene) (rr-P3HT) by quantum mechanical (QM) and molecular dynamics (MD) methods. In particular, we clarify the effects associated with the respective contribution from the ordered and disordered regions. In the ordered regions, the typical value of the hole mobility along the intrachain route is about 1 cm(2) V(-1) s(-1), which is significantly larger than that along the pi-pi interchain route, approximately 10(-2) cm(2) V(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
135
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 35 publications
10
135
0
Order By: Relevance
“…The expected qualitative trend in mobility has been replicated; the mobility of the ordered morphology is significantly greater than the mobility within the disordered morphologies. Furthermore, the pipeline has quantitatively predicted that the improvement in mobility is around three orders of magnitude, in reasonable agreement with experimental investigations which have demonstrated a 1-2 order of magnitude increase in time-of-flight and field-effect mobilities depending on processing conditions, crystallinity and morphological structure [139][140][141][142]. Additionally, the absolute values of the mobilities reported here are in good quantitative agreement with experimental results.…”
Section: Charge Mobilitysupporting
confidence: 89%
See 1 more Smart Citation
“…The expected qualitative trend in mobility has been replicated; the mobility of the ordered morphology is significantly greater than the mobility within the disordered morphologies. Furthermore, the pipeline has quantitatively predicted that the improvement in mobility is around three orders of magnitude, in reasonable agreement with experimental investigations which have demonstrated a 1-2 order of magnitude increase in time-of-flight and field-effect mobilities depending on processing conditions, crystallinity and morphological structure [139][140][141][142]. Additionally, the absolute values of the mobilities reported here are in good quantitative agreement with experimental results.…”
Section: Charge Mobilitysupporting
confidence: 89%
“…A possible reason for this could be that, while qualitative agreement with experiment is common, quantitative agreement can vary significantly depending on the system studied. In general, calculated mobility values are often more accurate in small molecule systems where transfer integrals are averaged over, or an initial configuration is assumed [141,149,150]. Otherwise, these computational methods tend to overpredict the time-of-flight mobilities of material systems by two to six orders of magnitude, with more noticeable discrepancies for larger or more complex molecules with a greater quantity of physical conformations, such as polymer chains [75,80,151,152].…”
Section: Charge Mobilitymentioning
confidence: 99%
“…In contrast, the connection of "face-to-face", side-chains, different oriented crystalline regions and disordered regions are all larger barriers for hopping of carriers ( Figure 3I). Secondly, the tie chains connecting adjacent crystalline regions (Figure 1b) play an important role in decrease the transport barrier of carriers at grain boundary [43][44][45]. As known, the disordered regions between adjacent ordered domains limit the efficient transport of carriers.…”
Section: Connectivity Between Crystalline Regionsmentioning
confidence: 97%
“…As known, the disordered regions between adjacent ordered domains limit the efficient transport of carriers. Lan et al reported that there were three modes for chains in disordered regions between adjacent crystalline regions: extending, looping, and bridging chains [43]. In the disordered domains, the charge transport can occur in the interchain pathway by hopping between close enough chain ends/loops or in the intrachain pathway along the bridging chains.…”
Section: Connectivity Between Crystalline Regionsmentioning
confidence: 99%
“…When represented by a two-dimensional model, it showed that a phase separated morphology with feature sizes smaller than ~50 nm could improve charge transport within and between the two phases and reduce bimolecular charge recombination [6]. In the case of P3HT/PCBM, the molecular ordering of rr-P3HT is concerned with photon absorption and hole transport [7][8][9], and the suitable size of phase separation is related to charge separation. In order to achieve an optimum morphology, many methods have been employed, including thermal annealing [10,11], solvent vapor annealing [12][13][14], mixed solvent [15,16], introduction of additives [17,18] and so on.…”
mentioning
confidence: 99%